Molecular and Phylogenetic Analyses of the Mediator Subunit Genes in Solanum lycopersicum - Wang, Yunshu; Liang, Honglian; Chen, Guoping; Liao, Changguang; Wang, Yicong; Hu, Zongli; Xie, Qiaoli (Frontiers in Genetics, 2019)
The Mediator complex is a multi-subunit protein assembly that serves as a central scaffold to help regulate DNA-binding transcription factors (TFs) and RNA polymerase II (Pol II) activity controlled gene expression programmed in response to developmental or environmental factors. However，litter information about Mediator complex subunit (MED) genes in tomato is available, although it is an essential model plant. In this study, we retrieved 46 candidate SlMED genes from the genome of tomato, and a comprehensive analysis was conducted, including their phylogenetic relationship, chromosomal locations, gene structure, cis-regulatory elements prediction as well as gene expression. The expression profiling of 46 SlMED genes was analyzed using publicly available RNA-seq data. Furthermore, we selected some SlMED genes to evaluate their expression patterns in various tissues and under different abiotic stress treatments by qRT-PCR experiments. This is the first detailed report to elucidate the molecular and phylogenetic features of the MED genes in tomato, and it provides valuable clues for further functional analysis in order to clarify the role of the SlMED genes in diverse plant growth, development and abiotic stress response.